Learning from storybooks : does the theme matter? - Kara, Hatice Şeyma. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
Reading storybooks are one of the most preferred pastime activities in childhood. In addition to entertaining feature, storybooks can be used to improve children’s social and cognitive skills. However, there is limited research on whether and what kind of information children can learn from storybooks and what kind of storybooks promote this learning process. Study 1 investigated whether story theme (i.e., realistic, anthropomorphic, or fantastical) and the problem context (i.e., physical or social) influence children’s learning of analogical problem solutions. In Study 1, 91 preschool children listened to storybooks and were asked to solve problem solution analogies. Results showed that children who listened to realistic stories were more successful while solving physical problem solution analogies. However, this was not the case for the stories which had more social context. In Study 2, we examined whether story theme has an impact on children’s learning of pro-social behaviors such as sharing, helping and honesty. Seventy-eighty 6-year-old children were administered pro-social behavioral tasks before and after listening to either realistic, anthropomorphic or fantastical storybooks. It was found that children who listened to realistic storybooks showed an increase in their sharing behavior from pre-test to post-test compared to children in either anthropomorphic or fantastical conditions. Even though we did not find this kind of story theme effect on children’s helping or honesty behaviors, children’s scores on these behaviors increased from pre to posttests which suggested that listening to storybooks promoted children’s prosocial behaviors.
Keywords: Anthropomorphism.; Social interaction in children.; Storytelling Fiction.; Storytelling ability in children.